Female English Teachers Perceptions and Experience of Continuing Professional Development in Qatar - Saba Qadhi; Alan Floyd (MDPI AG, 2021)
The Qatari government views English language learning as crucial to the country's future success. Anecdotal evidence suggests, however, that English language teachers (ELTs) employed in Qatar may not necessarily have the appropriate training, qualifications, and experience to enable them to teach successfully. Despite growing research and interest in the continuing professional development (CPD) experiences and needs of ELTs in Western contexts, there remains a lack of research in Middle Eastern countries in general and in Qatar in particular. The aim of this study was to address this gap by exploring female ELTs' perceptions and experiences of CPD in Qatar in order to develop new practical and theoretical insights into our understanding of this area. The study draws on data from life history interviews undertaken with 16 female ELTs with at least 3 years of teaching experience in Qatari schools. The study found that the participants had very different experiences of CPD based on their personal and professional characteristics. This suggests that for it to be perceived as a positive experience, the current model of professional development for ELTs may need revising. We propose a paradigm shift from a traditional "one size fits all" CPD model towards a more dynamic and interactive style of teacher development that facilitates both personal reflection and professional discourse among teachers. It is argued that such a shift would prove a considerable step forward for English language teaching in this country.